Triple-hit high-grade B-cell lymphoma presenting with ovarian torsion. Issue 5 (31st May 2021) - Osataphan, Soravis; Augustynowicz, Aleksandra; Perrino, Carmen; Lam, Prudence
Abstract : We report a case of a previously healthy woman in her early 70s who presented with 2 weeks of episodic abdominal pain and significant weight loss. Imaging of her abdomen revealed acute right ovarian torsion associated with bilateral ovarian enlargement and an indeterminant pelvic mass. An urgent laparoscopic bilateral oophorectomy was performed with pathological results consistent with triple-hit high-grade B-cell lymphoma. She was successfully treated with dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin and rituximab, intrathecal methotrexate and venetoclax with complete remission after three cycles. Ovarian lymphoma is a rare entity and its genetic features have not been well described. We performed a literature review, describe the current knowledge regarding ovarian lymphoma and its therapeutic implication in the genomic age.